Brain metabolites in cholinergic and glutamatergic pathways are altered by pancreatic cancer cachexia. Issue 6 (2nd October 2020) - Winnard, Paul T.; Bharti, Santosh Kumar; Sharma, Raj Kumar; Krishnamachary, Balaji; Mironchik, Yelena; Penet, Marie‐France; Goggins, Michael G.; Maitra, Anirban; Kamel, Ihab; Horton, Karen M.; Jacobs, Michael A.; Bhujwalla, Zaver M.
Abstract: Background: Cachexia is a major cause of morbidity in pancreatic ductal adenocarcinoma (PDAC) patients. Our purpose was to understand the impact of PDAC‐induced cachexia on brain metabolism in PDAC xenograft studies, to gain new insights into the causes of cachexia‐induced morbidity. Changes in mouse and human plasma metabolites were characterized to identify underlying causes of brain metabolic changes. Methods: We quantified metabolites, detected with high‐resolution 1 H magnetic resonance spectroscopy, in the brain and plasma of normal mice ( n = 10) and mice bearing cachexia ( n = 10) or non‐cachexia ( n = 9) inducing PDAC xenografts as well as in human plasma obtained from normal individuals ( n = 24) and from individuals with benign pancreatic disease ( n = 20) and PDAC ( n = 20). Statistical significance was defined as a P value ≤0.05. Results: The brain metabolic signature of cachexia‐inducing PDAC was characterized by a significant depletion of choline of −27% and −21% as well as increases of glutamine of 13% and 9% and formate of 21% and 14%, relative to normal controls and non‐cachectic tumour‐bearing mice, respectively. Good to moderate correlations with percent weight change were found for choline ( r = 0.70), glutamine ( r = −0.58), and formate ( r = −0.43). Significant choline depletion of −38% and −30%, relative to normal controls and non‐cachectic tumour‐bearing mice, respectively, detected in the plasma of cachectic mice likely contributed to decreased brain choline in cachectic mice. Similarly, relative to normal controls and patients with benign disease, choline levels in human plasma samples of PDAC patients were significantly lower by −12% and −20% respectively. A comparison of plasma metabolites from PDAC patients with and without weight loss identified significant changes in glutamine metabolism. Conclusions: Disturbances in metabolites of the choline/cholinergic and glutamine/glutamate/glutamatergic neurotransmitter pathways may contribute to morbidity. Metabolic normalization may provide strategies to reduce morbidity. The human plasma metabolite changes observed may lead to the development of companion diagnostic markers to detect PDAC and PDAC‐induced cachexia.